Chromosome-scale scaffolding of the black raspberry (Rubus occidentalis L.) genome based on chromatin interaction data. Issue 1 (7th February 2018) - Jibran, Rubina; Dzierzon, Helge; Bassil, Nahla; Bushakra, Jill M; Edger, Patrick P; Sullivan, Shawn; Finn, Chad E; Dossett, Michael; Vining, Kelly J; VanBuren, Robert; Mockler, Todd C; Liachko, Ivan; et al.
Abstract: Black raspberry ( Rubus occidentalis L.) is a niche fruit crop valued for its flavor and potential health benefits. The improvement of fruit and cane characteristics via molecular breeding technologies has been hindered by the lack of a high-quality reference genome. The recently released draft genome for black raspberry (ORUS 4115-3) lacks assembly of scaffolds to chromosome scale. We used high-throughput chromatin conformation capture (Hi-C) and Proximity-Guided Assembly (PGA) to cluster and order 9650 out of 11, 936 contigs of this draft genome assembly into seven pseudo-chromosomes. The seven pseudo-chromosomes cover ~97.2% of the total contig length (~223.8 Mb). Locating existing genetic markers on the physical map resolved multiple discrepancies in marker order on the genetic map. Centromeric regions were inferred from recombination frequencies of genetic markers, alignment of 303 bp centromeric sequence with the PGA, and heat map showing the physical contact matrix over the entire genome. We demonstrate a high degree of synteny between each of the seven chromosomes of black raspberry and a high-quality reference genome for strawberry ( Fragaria vesca L.) assembled using only PacBio long-read sequences. We conclude that PGA is a cost-effective and rapid method of generating chromosome-scale assemblies from Illumina short-read sequencing data. Plant genomics: Improved genome for the black raspberry: Assembly of a high-quality reference genome for the black raspberry plant will inform future crop improvements. Sequencing the genomes of widely-grown, profitable fruit crops can help researchers identify the DNA markers linked to desirable traits, potentially improving crop health and yields. David Chagné at the New Zealand Institute for Plant and Food Research Limited and co-workers combined new techniques to significantly improve on an existing genome for the black raspberry (Rubus occidentalis L.). The researchers used Hi-C analysis to create a map identifying the interactions between chromatin fragments – macromolecules made from DNA, proteins and RNA – and the three-dimensional structure of chromosomes inside the cell nucleus. Then, they used a bioinformatics assembly method to construct the genome from this data. The new genome showed high accuracy when compared to another genome from the same family.